Prevalence of Knee Dysfunction in Mallakhamb Players in Karad (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Mallakhamb is combination of Yoga, Gymnastics and Martial Arts. There is various typesof mallakhamb such as pole, rope, hanging, niradhar(without support), on cane, on floating platform,mallakhamb with weapons etc. but at competitive level only pole, rope and hanging mallakhamb are beingperformed by mallakhamb player.In the sport , knee is common injury site. Knee dysfunction leads tolong absence from sports and are one of the main causes of permanent sports disability. Common cause ofmusculoskeletal pain is hypermobility. In mallakhamb players knee dysfunction is diagnosed with the helpof KOOS scale. Conservative management is important to correct knee dysfunctions in mallakhamb players.This study has been undertaken to check the prevalence of knee dysfunction in mallakhamb players.Objective: To find out the prevalence of knee dysfunction in mallakhamb players.Method: An observational study was carried out using a cross sectional study design. The studyconducted in and around karad, Maharashtra. The samples were chosen using the simple random sampling method.The participants in this study were both males and females who were played state and national level mallakhambgame more than 6years. Subjects who played only national level mallakhamb game and subjects who were notwilling to participate in mallakhamb were excluded from this study. Study was conducted using a sample size of 84mallakhamb players (n= 4pq/L2 ) for a period of 6 months. The materials was used in this study includes paper, pen,data collection sheet, consent form.Results: On the basis of statistical analysis there was significant knee dysfunction in mallakhamb players.Conclusion; After analyzing the data, it was concluded that there is a prevalence of knee dysfunction inmallakhamb players.